2016
DOI: 10.1155/2016/3216246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Systemic and Regional Use of Magnesium Sulfate on Postoperative Tramadol Consumption in Lumbar Disc Surgery

Abstract: Aim. To investigate the effect of magnesium administered to the operative region muscle and administered systemically on postoperative analgesia consumption after lumbar disc surgery. Material and Method. The study included a total of 75 ASA I-II patients aged 18–65 years. The patients were randomly allocated into 1 of 3 groups of 25: the Intravenous (IV) Group, the Intramuscular (IM) Group, and the Control (C) Group. At the stage of suturing the surgical incision site, the IV Group received 50 mg/kg MgSO4 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 22 publications
(26 reference statements)
1
34
0
Order By: Relevance
“…These effects mediated through its antinociceptive properties as a noncompetitive N-methyl-D-aspartate receptor antagonist. [ 6 7 8 9 10 11 12 ] In addition to its role in procedures that necessitate deliberate hypotension as it acted as a calcium channel blocker and direct vasodilator. [ 13 14 ] Hence, it possibly controls the undesirable effects of succinylcholine and endotracheal intubation such as increased IOP, hypertension, and tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…These effects mediated through its antinociceptive properties as a noncompetitive N-methyl-D-aspartate receptor antagonist. [ 6 7 8 9 10 11 12 ] In addition to its role in procedures that necessitate deliberate hypotension as it acted as a calcium channel blocker and direct vasodilator. [ 13 14 ] Hence, it possibly controls the undesirable effects of succinylcholine and endotracheal intubation such as increased IOP, hypertension, and tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 10 RCTs that studied drugs locoregionally administered to prevent and treat postoperative pain after lumbar spine procedures, 5 tested morphine in various combinations and dosages, 2 tested ropivacaine, 1 tested levobupivacaine, 1 tested fentanyl, and 1 tested MgSO 4 injection . Of the 5 RCTs that tested morphine, morphine administration led to a reduction of analgesic consumption when compared to the control group in 4 studies, while Yen et al found that there was no difference in opioid consumption between extended‐release epidural morphine 10 mg and 15 mg .…”
Section: Resultsmentioning
confidence: 99%
“…Ropivacaine effectively reduced pain intensity and proved to be more effective when combined with dexamethasone given caudally than systemic dexamethasone . Levobupivacaine, epidural fentanyl, and MgSO 4 injection led to positive results for postoperative pain prevention and treatment …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations